Comparison of cyclooxygenase 2 expression in adenocarcinomas of the gastric cardia and distal oesophagus. Issue 12 (21st November 2003) - Buskens, C J; Sivula, A; van Rees, B P; Haglund, C; Offerhaus, G J A; van Lanschot, J J B; Ristimäki, A
Abstract : Background: Adenocarcinomas of the gastric cardia and distal oesophagus are at present often considered as one clinical entity because of their comparable increasing incidence, prognosis, and optimal treatment options. However, it is still a matter of debate whether these malignancies have the same pathogenesis and genotype. Aims: The aim of this study was to analyse expression of cyclooxygenase 2 (COX-2) in cardia carcinomas, and correlate this expression with clinicopathological parameters and survival. The results were compared with the prognostic value of COX-2 found for Barrett carcinomas. Methods: Tumour sections of 134 consecutive patients undergoing potentially curative surgery for an adenocarcinoma of the gastric cardia and substantially invading the distal oesophagus were immunohistochemically stained using a COX-2 monoclonal antibody. Specimens were blindly scored based on intensity and extent of COX-2 immunopositivity. Results: COX-2 expression was negative to weak in 59% ("COX-2 low") and moderate to strong in 41% ("COX-2 high") of tumours. This was significantly lower than in Barrett carcinomas (p<0.0001). COX-2 expression was not correlated with any clinicopathological parameter. A correlation between elevated COX-2 expression and reduced survival, as described for Barrett carcinomas, was not identified for cardiac carcinomas. Conclusions: There is a difference in COX-2 expression with respect to intensity and prognostic significance between adenocarcinomas of the gastric cardia and distal oesophagus. This suggests a different pathogenesis and different genetic constitution of these two cancers. Based on these findings, the role of selective COX-2 inhibitors in the treatment of adenocarcinomas of the gastric cardia is less promising than in Barrett carcinomas.